Why does the amount of income redistribution differ between United States and Europe? The Janus face of Switzerland - Sule Akkoyunlu; Ilja Neustadt; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2009)
In this paper, the amount of income redistribution in the United States, the European Union, and Switzerland is compared and empirically related to economic, political, and behavioral determinants elaborated in the literature. Lying in between the two poles, Switzerland provides unique evidence about the relative merits of competing hypotheses. It tips the balance against the economic explanation, which predicts more rather than less income redistribution in the United States compared to the EU. It only weakly supports the political model linking proportional representation and multiparty structure (which also characterize Switzerland) to redistribution; yet the Swiss share of transfers in the GDP is low. Behavioral explanations receive a good deal of support from the case of Switzerland, a country that shares with the United States the belief that hard work rather than luck, birth, connections, and corruption determine wealth. In this way, the Janus face of Switzerland may help to explain the difference in the amount of U.S. and EU income redistribution.
Keywords: D31; D63; D64; H53; I31; 330; Redistribution; Income Mobility; Openness; Political Economy; Beliefs; Religion; Immigration; Einkommensverteilung; Soziale Mobilität; Verteilungswirkung; Politisches System; Religion; Soziale Werte; Einwanderung; Vergleich; USA; Europa; Schweiz